Analisis Pengaruh Pembiayaan Murabahah, Tingkat Bagi Hasil Dan Suku Bunga Acuan BI Terhadap Volume Pembiayaan Mudharabah Perbankan Syariah Di Indonesia (Periode 2016-2018) - Widyastuti, Emy (AKTSAR: Jurnal Akuntansi Syariah, 2019)
The purpose of this study is to analyze the influence of murabahah financing, profit-sharing rate and BI rate on the volume of Islamic banking mudharabah financing in Indonesia during the period of 2016-2018. The sample used in this study is all Islamic Commercial Banks in Indonesia in 2016-2018. The data analysis method used in this study is multiple linear regression to find the effect of each variable on the volume of mudharabah financing of Islamic banking in Indonesia. The results showed that simultaneously murabahah financing variables, profit-sharing rates, and BI reference interest rates influenced mudharabah financing. While partially murabahah financing variable and BI reference interest rate have a significant negative effect on mudharabah financing, while the interest rate variable has a significant positive effect on mudharabah financing. The limitation of this study is that it uses a few variables so that it has not been able to show the full variables that affect mudharabah financing volume.